1978
DOI: 10.1172/jci109199
|View full text |Cite
|
Sign up to set email alerts
|

The stimulus-secretion coupling of glucose-induced insulin release. Metabolic and functional effects of NH4+ in rat islets.

Abstract: A B S T R AC T NH4+ caused a dose-related, rapid, and reversible inhibition of glucose-stimulated insulin release by isolated rat islets. It also inhibited glyceraldehyde-, Ba2+-, and sulfonylurea-stimulated insulin secretion. NH4 failed to affect glucose utilization and oxidation, glucose-stimulated proinsulin biosynthesis, the concentration of ATP, ADP, and AMP, and the intracellular pH. NH4+ also failed to affect the ability oftheophylline and cytochalasin B to augment glucoseinduced insulin release. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…The opposite effects were observed on intracellular alkalinization with NH 4 Cl. Similar results were reported in a number of other studies performed on mouse islets and insulinoma cell lines as well as on rat islets (12,13,(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The opposite effects were observed on intracellular alkalinization with NH 4 Cl. Similar results were reported in a number of other studies performed on mouse islets and insulinoma cell lines as well as on rat islets (12,13,(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
“…In seeking the crucial difference between the two buffers, we noted that islets maintain a lower intracellular pH in HEPES-buffered media than in HCO 3 Ϫ -buffered media (8 -11). Furthermore, other studies have reported that a lower intracellular pH in the ␤-cell favors nutrient-induced insulin release and related functions, whereas an increase of intracellular pH has an inhibitory effect (12)(13)(14)(15)(16)(17)(18)(19)(20). In this study, we confirmed that the presence of HEPES in the medium results in a significant decrease in intracellular pH in islets.…”
mentioning
confidence: 99%
“…Yeast (Saccharomyces cerevisiae) mutants, defective in Mep homologues, were earlier used to clone and characterize AMT homologues from plants and humans by functional complementation [11,14]. Yet, no specific NH þ 4 /NH 3 transporter, operating at elevated NH þ 4 /NH 3 concentrations, has been isolated or characterized in any organism.…”
Section: Introductionmentioning
confidence: 99%
“…Malaisse and co-workers have demonstrated changes in wholetissue concentrations of reduced nicotinamide nucleotides in islets exposed to stimulatory concentrations of glucose (Malaisse et al, 1979a,b) or pyruvate (Veech et al, 1969). A possible role for the availability of reduced nicotinamide nucleotides in stimulus-secretion coupling was further supported by the use of agents such as menadione and NH4+, which lowered islet content of reduced nicotinamide nucleotides and inhibited insulin release (Malaisse et al, 1978a,b;Sener et al, 1978a). Again, however, these studies could not give unequivocal information on the identity and cellular location of the redox couple(s) affected.…”
mentioning
confidence: 99%